Membangun Jejak Digital UMKM Desa Wiro Bayat : Optimalisasi QRIS dan Google Business Profile untuk Meningkatkan Visibilitas, Akses Pasar, dan Daya Saing Usaha - Mar’atu Rosyada Al Fariz; Nurul Amiliana; Rika Ramadhana; Salsabilla Indy Eka Putri; Mochammad Achwan Baharuddin; Faizal Jannu Aryanto Sahidana Putra (Universitas Pahlawan Tuanku Tambusai, 2026)
Seblak Prasmanan Express MSME in Wiro Village, Bayat, still relies on cash transactions and does not yet have a digital identity, resulting in low business visibility, limited market access, and reduced competitiveness compared to MSMEs that have adopted digital platforms. This community service activity aims to build the MSME's digital footprint through the optimization of QRIS and Google Business Profile to enhance business visibility, market access, and competitiveness. The method employed is based on a community empowerment approach, including community education, training, science and technology diffusion, mediation, and advocacy, implemented gradually and sustainably. The results indicate that the activation of QRIS through the DANA application facilitates cashless transactions, while the creation of a Google Business Profile makes the business easier to find through Google Search and Google Maps. The assistance program also includes strengthening social media content, utilizing WhatsApp Business, and establishing consistent operating hours. Therefore, this digital assistance has proven effective in strengthening the MSME's digital identity, expanding market reach, and enhancing its competitiveness sustainably in the digital economy era.